2018
DOI: 10.1016/j.jiph.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of MERS-CoV-specific RNA and antibodies in animals that have had contact with MERS patients in Saudi Arabia

Abstract: These findings indicate that camels are a significant reservoir for the maintenance of MERS-CoVs, and they are an important source of human infection with MERS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 37 publications
6
48
3
Order By: Relevance
“…In a study conducted across Burkina Faso, Morocco and Ethiopia, dromedaries used for milk and meat had higher seroprevalence than those used for transport (Miguel et al, 2017). In most of the studies that stratified by sex, little difference was seen, but in Kenya females had statistically significantly higher seroprevalence than males (93% vs. 81% in one study (Munyua et al, 2017), and 74% vs. 54% in another (Ommeh et al 2018)) whereas males had significantly higher seroprevalence in Egypt and in KSA (72% and 84% in males vs. 66% in females) (Ali et al, 2017b;Kasem et al, 2018b).…”
Section: Sample Population Characteristicsmentioning
confidence: 91%
See 2 more Smart Citations
“…In a study conducted across Burkina Faso, Morocco and Ethiopia, dromedaries used for milk and meat had higher seroprevalence than those used for transport (Miguel et al, 2017). In most of the studies that stratified by sex, little difference was seen, but in Kenya females had statistically significantly higher seroprevalence than males (93% vs. 81% in one study (Munyua et al, 2017), and 74% vs. 54% in another (Ommeh et al 2018)) whereas males had significantly higher seroprevalence in Egypt and in KSA (72% and 84% in males vs. 66% in females) (Ali et al, 2017b;Kasem et al, 2018b).…”
Section: Sample Population Characteristicsmentioning
confidence: 91%
“…Age stratified studies in KSA and Jordan found that juveniles had a higher RNA-positivity than adults (Alagaili et al, 2014;van Doremalen et al, 2017;Kasem et al, 2018b). RNA-positivity also had an inverse association with age in dromedaries across Morocco, Burkina Faso and Ethiopia (Miguel et al, 2017).…”
Section: Agementioning
confidence: 97%
See 1 more Smart Citation
“…A study 25 of animal herds associated with patients with MERS-CoV infection in Saudi Arabia found that the nasal swabs of 75 of 584 dromedary camels were positive for MERS-CoV RNA for about 2 weeks, whereas the nasal swabs were negative for MERS-CoV RNA in other animals, including goats, sheep, and cattle. Notably, 70·9% of camels associated with individuals with MERS-CoV infections had MERS-CoV antibodies as determined by ELISA assays, and full genome sequencing identified ten MERS-CoV camel isolates that were identical to the isolates of their corresponding 25 Nevertheless, testing of sera from 191 people with various degrees of exposure to an infected dromedary herd found no serological evidence of infection. 26 These data suggest that although MERS-CoV infection is widespread among dromedary camels, zoonotic transmission of MERS-CoV from camels to human beings is relatively uncommon, and human disease burden is not directly proportional to potential exposure to camels.…”
Section: Transmission From Camels To Human Beingsmentioning
confidence: 99%
“…Since September 2012, 27 countries have reported cases of MERS and WHO has been notified of 2079 laboratory-confirmed cases with at least 722 deaths by the end of August 2017 [2]. MERS coronavirus (MERS-CoV) is a novel virus from camels [6,10,11], but the mechanisms of direct or indirect zoonotic transmission have yet to be known.…”
Section: Introductionmentioning
confidence: 99%